Examining the Genomic Influence of Skin Antioxidants In Vitro - James V. Gruber; Robert Holtz (Hindawi Limited, 2010)
A series of well-known, purified antioxidants including: Resveratrol, Epigallocatechin Gallate (EGCG), Genistein, Rosavin, Puerarin, Chlorogenic Acid, Propolis and two newer unexplored isoflavonoids isolated from Maclura pomifera (Osage Orange) including Pomiferin and Osajin, were applied to Normal Human Dermal Fibroblasts (NHDF) and Normal Human Dermal Keratinocytes (NHEK) for 24 hours. The resulting treated cells were then examined using human gene microarrays supplied by Agilent. These chips typically have somewhere on the order of 30,000 individual genes which are expressed in the human genome. For our study, this large list of genes was reduced to 205 principal genes thought to be important for skin and each individual ingredient was examined for its influence on the culled list of genes. Working on a hypothesis that there may be some common genes which are either upregulated or downregulated by all or most of these ingredients, a short list of genes for each cell line was developed. What appears to emerge from these studies is that several genes in the gene pool that was screened are influenced by most or all of the molecules of interest. Genes that appear to be upregulated in both cell lines by all the ingredients include: ACLY, AQP3, COX1, NOS3, and PLOD3. Genes that appear to be downregulated in both cell lines by all ingredients include only PGR.